Hydrangea-like multi-scale carbon hollow submicron spheres with hierarchical pores for high performance supercapacitor electrodes. (10th September 2015) - Guo, Daying; Chen, Xi'an; Fang, Zhipeng; He, Yufeng; Zheng, Cong; Yang, Zhi; Yang, Keqin; Chen, Ying; Huang, Shaoming
Graphical abstract: Highlights: Uniform hydrangea-like multi-scale carbon hollow submicron spheres are fabricated. HCSSg contains carbon nanosheets (about 10 nm thickness) and mesoporous channels. HCSSg with hierarchical pores possesses high surface area and bulk density. HCSSg exhibits high gravimetric and outstanding volumetric capacitive performance. HCSSg demonstrates good rate capability and cycle stability. Abstract: Uniform hydrangea-like multi-scale carbon hollow submicron spheres (HCSSg) are fabricated by a simple hydrothermal method using glucose as carbon source and fibrous silicon dioxides spheres as shape guide. Structure characterization suggests that petal-like partially graphitized carbon nanosheets with the thickness of about 10 nm arranged in three dimensions (3D) to form the hydrangea-like hollow spheres (size ranging from 250 to 500 nm) with mesoporous channels, which can be conducive to be a high specific surface area (934 m 2 g −1 ) and bulk density (0.87 cm g −3 ), hierarchical pores structure with good conductivity. As a result, the HCSSg has been demonstrated to be a supercapacitor electrode material with high gravimetric (386 F g −1 at 0.2 A g −1 ) and outstanding volumetric (335 F cm −3 ) capacitance, good rate capability and cycling stability with 94% capacitance retention after 5000 cycles in aqueous electrolytes, thus suggesting its application potential.